2007
DOI: 10.1063/1.2822399
|View full text |Cite
|
Sign up to set email alerts
|

Optical transitions in polarized CdSe, CdSe∕ZnSe, and CdSe∕CdS∕ZnS quantum dots dispersed in various polar solvents

Abstract: The optical transitions in ensembles of colloidal CdSe-based quantum dots (QDs) have been systematically studied as a function of the net QDs’ polarity/polarization and of the solvent’s polarity. While the general trend observed for all QD systems dispersed in different solvents is similar, the spectral shifts are more pronounced in core QDs than in core/shell structures. Our results can be rationalized by taking account of the electric field experienced by the QDs that results from their effective polarizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 26 publications
0
30
0
Order By: Relevance
“…Commonly, such a blueshift is assigned to a decrease of particle size, which is in the present case very likely caused by oxidation of the particle surface 3, 22. However, spectral shifts can also occur if the polarity of the QD changes in a given electric field by the Stark effect 48. In principle, this is also possible if under photoactivation the number and charge of solvent and oxygen molecules changes in the vicinity of the QD.…”
Section: Resultsmentioning
confidence: 76%
“…Commonly, such a blueshift is assigned to a decrease of particle size, which is in the present case very likely caused by oxidation of the particle surface 3, 22. However, spectral shifts can also occur if the polarity of the QD changes in a given electric field by the Stark effect 48. In principle, this is also possible if under photoactivation the number and charge of solvent and oxygen molecules changes in the vicinity of the QD.…”
Section: Resultsmentioning
confidence: 76%
“…It is known that spectral diffusion occurs in the temporal evolution of the fluorescence emission of individual NPs. 41 Spectral diffusion broadens the fluorescence spectra when it happens on time scales smaller than the integration time, i.e., the single-particle line shapes result from rapid spectral shifting of the emission peak. 24 When spectral diffusion occurs on time scales larger than the integration time, it is visible as jumps of the whole spectrum.…”
Section: The Very Same Nps Under Subsequent Exchange Of Ethylene Glycolsmentioning
confidence: 99%
“…The absorption peak positions of these QDs were very similar while the emission peaks showed modest differences, as is commonly observed after surface modification. [17][18][19] Dynamic light scattering data indicated that QDs had comparable sizes, ranging from 7.5 to 11.7 nm, with PEG-QD having a slightly larger hydrodynamic size of 24 nm, presumably due to modest level of aggregation (see ESI † for QD physicochemical properties).…”
mentioning
confidence: 99%